1968
DOI: 10.1364/ao.7.000001
|View full text |Cite
|
Sign up to set email alerts
|

Photon Counting

Abstract: The fundamentals of photon counting using photomultipliers are described, including criteria for selecting suitable photomultipliers, some of the precautions that must be taken in using these devices, and methods of calculating the counting errors that may occur under various conditions of measurement. Problems of determining the time distribution of photons and, in particular, the coincident emission of photons which may be encountered in lasers and other simulated emission sources are also discussed. The que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(25 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…In time-of-flight laser-ranging, the timing jitter of the detector will affect the depth resolution of the measurement [93] while in QKD, the timing jitter can lead to intersymbol interference and increase the error rate of the key exchange process [94]. Figure 12 shows a representational diagram of the operation of possibly the earliest form of single-photon detector to be used in a wide-range of applications; the photomultiplier tube (PMT) [95][96][97][98]. The device is formed from a vacuum tube with a photocathode at the entrance and a series of following dynodes arranged prior to an anode at the far end.…”
Section: Characterization Parametersmentioning
confidence: 99%
“…In time-of-flight laser-ranging, the timing jitter of the detector will affect the depth resolution of the measurement [93] while in QKD, the timing jitter can lead to intersymbol interference and increase the error rate of the key exchange process [94]. Figure 12 shows a representational diagram of the operation of possibly the earliest form of single-photon detector to be used in a wide-range of applications; the photomultiplier tube (PMT) [95][96][97][98]. The device is formed from a vacuum tube with a photocathode at the entrance and a series of following dynodes arranged prior to an anode at the far end.…”
Section: Characterization Parametersmentioning
confidence: 99%
“…Arising from the fact that photons follow Bose-Einstein statistics, the Poisson distribution is a good approximation to the number of photons arriving at the photocathode within a defined time window [16,17]. As the photoemission process follows the binomial distribution (with the quantum efficiency quantifying the probability of one photon producing one photoelectron), it has been shown that the number of photoelectrons n produced in the photocathode also follows a Poisson distribution [16] Pðl; nÞ ¼…”
Section: Methodsmentioning
confidence: 99%
“…Relatively few experimental studies on the SER characteristics (charge and transit time dispersions, etc.) have been reported, and the available data are still quite scarce [29].…”
Section: I Single-photon Detectorsmentioning
confidence: 99%